2020
DOI: 10.1111/1752-1688.12817
|View full text |Cite
|
Sign up to set email alerts
|

Lake Water Levels and Associated Hydrologic Characteristics in the Conterminous U.S.

Abstract: Establishing baseline hydrologic characteristics for lakes in the United States (U.S.) is critical to evaluate changes to lake hydrology. We used the U.S. Environmental Protection Agency National Lakes Assessment 2007 and 2012 surveys to assess hydrologic characteristics of a population of ~45,000 lakes in the conterminous U.S. based on probability samples of ~1,000 lakes/yr distributed across nine ecoregions. Lake hydrologic study variables include water‐level drawdown (i.e., vertical decline and horizontal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 83 publications
0
13
0
Order By: Relevance
“…The approach used to measure and describe various dimensions of littoral and riparian physical habitat is described in [43][44][45][46]. These measurements result in indicators of lake habitat complexity, shallow water habitat alteration, riparian vegetation cover, lakeshore disturbance, and lake drawdown exposure in the littoral zone [30,45,46]. The shallow water habitat alteration indicator is based on visual estimates of the areal cover of several types of natural cover (e.g., snags, macrophytes, overhanging vegetation) observed in the littoral zone around each lake.…”
Section: Indicator Development and Evaluationmentioning
confidence: 99%
“…The approach used to measure and describe various dimensions of littoral and riparian physical habitat is described in [43][44][45][46]. These measurements result in indicators of lake habitat complexity, shallow water habitat alteration, riparian vegetation cover, lakeshore disturbance, and lake drawdown exposure in the littoral zone [30,45,46]. The shallow water habitat alteration indicator is based on visual estimates of the areal cover of several types of natural cover (e.g., snags, macrophytes, overhanging vegetation) observed in the littoral zone around each lake.…”
Section: Indicator Development and Evaluationmentioning
confidence: 99%
“…The goals of land and water management practices are strongly affected by underlying regional geoclimatic variation that influences spatial and seasonal patterns of water abundance, as illustrated by the distribution and density of dams across the landscape (Smith et al 2002; Doubek and Carey 2017; Fergus et al 2020). We found that the magnitude and direction of anthropogenic effects on lake hydrology varied across CONUS ecoregions particularly in the West and Midwest ecoregions.…”
Section: Discussionmentioning
confidence: 99%
“…Lakes with Evap : Inflow = 0 have all water entering the lake leaving as outflow, lakes with Evap : Inflow = 1 have all inflowing water lost to evaporation (100%), and lakes with Evap : Inflow > 1 are desiccating lakes with evaporation exceeding inflow. Details on lake water isotope collection, laboratory measurements, and Evap : Inflow estimation steps can be found in Brooks et al (2014) and the NLA 2012 Evap : Inflow estimates in Fergus et al (2020).…”
Section: Nla Surveysmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing studies show that the operation of engineered control structures has a signi cant effect on LWS dynamics by regulating lake out ows and dampening water level variability (Gibson et al 2006b;Yin et al 2013;Getirana et al 2020). The water balance in regulated lakes is also subject to other human-induced disturbances (e.g., within-lake ecological restoration, inter-basin water transfer, irrigation and other withdrawals), which complicate the operational schemes for lake regulation and alter the variations in LWS (Veijalainen et al 2010;Fergus et al 2019;Getirana et al 2020). The complicated hydrological behavior of regulated lakes brings challenges to understanding LWS dynamics and their response to the changing environment.…”
Section: Introductionmentioning
confidence: 99%